Pengaruh Media Sosial dalam Transaksi Jual Beli di Era Digital: The Influence of Social Media in Buying and Selling Transactions in the Digital era - Sinta Sari, Sinta Sari (Journal of Beauty and Cosmetology (JBC), 2022)
Digital buying and selling are all forms of trade transactions of goods or services using internet media. The development of buying and selling via the Internet that covers national and international in all corners of the world. Buying and selling transactions through digital is considered an effective and efficient sales medium that facilitates the transaction process for sellers or buyers. The development of science and technology (science and technology) in the current era of globalization is experiencing an increasingly rapid development as a result of the rapid growth of social media in today's modern era. Social media is a digital platform that facilitates its users to communicate directly or indirectly without any time limits. Buying and selling transactions through digital is considered an effective and efficient sales medium that facilitates the transaction process for sellers or buyers. The existence of social media can make developments increasingly increasing in various types and sectors, especially in the economic sector. People think that online transactions are easier and practical to do. Initially, people carried out online transaction activities when paying certain bills. Currently online transactions are carried out by the community to meet the needs of both primary, secondary and tertiary needs. Many people buy goods through online sites.Keywords: Social Media, Buying and selling transactions, dDigital Age